Pelatihan dan Pendampingan Digital Marketing Melalui Platform Marketplace dan Sosial Media Bagi UMKM Kerajinan Di Desa Ridan Permai Kecamatan Bangkinang Kota - Rahmad Akbar; Dzulhijjah Yetti; Merlia Rahmayani; Nurbit Nurbit; Harmi Yelmi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Problems that often occur in urban areas are business competition and lack of attractive marketing by MSMEs. In urban areas, there are many MSMEs but only a few are able to take advantage of digital marketing. In fact, digital marketing activities such as creating logos, product photos and promotions in the marketplace can have a positive impact on society. Apart from that, urban communities also often face the problem of a lack of creative ideas in product marketing. Digital Marketing is a solution for MSMEs to carry out digital marketing, even though they are hampered by the use of editing applications and social media. This limitation does not make MSMEs players give up on sales. They can do marketing via WhatsApp status which is easy to implement and facilitates communication. Digital Marketing is a way of marketing products on social media by utilizing various applications available on the internet, providing knowledge to reach a wide target market, and enabling MSMEs to develop through digital or social media.